The Impact of Online Social Capital in The Context of Social Commerce on Consumer Purchase Intention - Septivani, Mega Dwi; Gustiawan, Willson; Wardani, Rahmi (ABEC Indonesia, 2024)
This study aims to examine the influence of online social capital on consumer purchasing interest in thecontext of social commerce. The urgency of this study lies in the increasing number of active users on social media everyyear, making this social commerce trend increasingly growing, because more and more business actors are offering theirproducts and services through social media. This study employs a quantitative approach, focusing on primary data from asurvey of Padang State Polytechnic students as the population. The data is processed using the Structural Equation Model(SEM) to test the hypothesis with the SmartPLS 4.0 program. The results of the study indicate that online social capitalhas a positive effect on consumer purchasing interest. Through these findings, it is hoped that it will contribute tobusiness actors who have used social commerce in their marketing strategies, so that they can take the right policiesthrough the online social capital they have from the experience gained from consumers, and it is recommended forbusiness actors who have not used social commerce to be able to use it along with the massive use of social media today.